Mengenal Religi Para Bapak Leluhur Israel - Noh Ibrahim Boiliu; Irfan Feriando Simanjuntak (DIEGESIS: Jurnal Teologi Kharismatika, 2019)
This paper aims to describe the religion of the Israelite ancestors. The problem discussed in this paper is which God the Israelite ancestors worshiped. The approach is to analyze several sources of the Old Testament relating to Israelite religion. Even though the three Semitic religions of Judaism, Christianity and Islam worship the same God "El/ Allah", that does not mean that all three teachings are the same. The teachings are different because the beliefs of the three are based on tradition and the scriptures (which are considered each as a revelation) are different about the same 'El / Allah'. AbstrakTulisan ini bertujuan untuk mendeskripsikan religi para bapak leluhur Israel. Masalah yang dibahas dalam tulisan ini adalah Tuhan manakah yang disembah para bapak leluhur Israel. Pendekatannya adalah menganalisis beberapa sumber Perjanjian Lama berkaitan dengan agama Israel. Sekalipun ketiga agama Semitik Yahudi, Kristen dan Islam menyembah Tuhan El/Allah yang sama, itu tidak berarti bahwa semua pengajaran/aqidah ketiganya sama. Pengajaran/aqidah berbeda karena kepercayaan ketiganya didasarkan tradisi dan kitab suci (yang dianggap masing-masing sebagai wahyu) berbeda mengenai El/Allah yang sama itu.